Live cell imaging of macrophage/bacterium interaction demonstrates cell lysis induced by Corynebacterium diphtheriae and Corynebacterium ulcerans - Weerasekera, Dulanthi (BMC Res Notes, 2019)
OBJECTIVES: In frame of a study to characterize the interaction of human macrophage-like cells with pathogenic corynebacteria, Corynebacterium diphtheriae and Corynebacterium ulcerans, live cell imaging experiments were carried out and time lapse fluorescence microscopy videos were generated, which are presented here. DATA DESCRIPTION: The time lapse fluorescence microscopy data revealed new insights in the interaction of corynebacteria with human macrophage-like THP-1 cells. In contrast to uninfected cells and infections with non-pathogenic C. glutamicum used as a control, pathogenic C. diphtheriae and C. ulcerans showed highly detrimental effects towards human cells and induction of cell death of macrophages.